Authorship Issues in Publishing and Career Development Workshop - Patricia O'Sullivan; Sheila Chauvin; Fred Wolf; Deborah Richardson; Maria Blanco (Association of American Medical Colleges, 2013)
Abstract Introduction Authoring and publishing manuscripts for publication may expose junior scholars to challenging professional and ethical situations. Faculty members are often advised to determine authorship order when they start a manuscript, but there are times when it may not be possible to follow. Dialogue and discussion of various challenging authoring and publishing scenarios will help faculty clarify these issues and develop a broad repertoire of possible responses to the inevitable publishing dilemmas. To prepare this resource we sought guidance from the literature and the authorship standards that have been perpetrated by various professional groups. Methods This is a two-part faculty development workshop. One part is a PowerPoint presentation and the other part is a set of 48 scenarios with responses. We include three ways in which the resources can be used depending on the context and level of experience of the learners. In all combinations the learners will review scenarios from actual experiences with a variety of responses to discuss the professional and ethical issues that arise. Results This workshop, at the time this guide was written, had been given three times in three different settings with three different instructors each using a different variation. In the initial offering, 90% of participants strongly agreed/agreed that the session was useful. Similarly in a presentation with educational fellows 100% strongly agreed/agreed that the workshop prepared them to make decisions about authorship. For an offering with faculty and students using strategy two, all those who responded (100%) to a brief survey thought the session and discussion were helpful and comments included: "It was a very useful presentation-example cases worked great", and "[The information] provided very helpful validation of my position on authorship to share with coauthors." Discussion While we believe that these successes attest to the versatility of the workshop, users should be attentive to adjustments that they need to make. Based on learner satisfaction reports from faculty using this resource in both the full and short versions we modified the offering by changing the strategy for using the scenario cards, developing alternative versions for novices and experienced individuals, and obtained ratings of the scenarios to help individuals customize their use of the scenarios.